Vulnerabilidade dos manguezais da Baía de Sepetiba a derrames de óleo na área portuária - Umezu, Ana Karina Augustinho de França (2019)
Since the wind acts directly on the spreading of the oil spill in incidents of spillage in the marine environment, the present study analyzed the importance of the wind variability in the port area of Sepetiba Bay in which are inserted mangroves of the metropolitan region of Rio de Janeiro. This study verified the behavior of the oily plume through deterministic scenarios previously established, observing the dispersion of the oil spot as a function of the recurrent wind data in the region for the summer and winter periods. We also analyzed the oil dispersion simulations in the Individual Emergency Plans (PEI) of the Port of Itaguaí and Southeast. The results of the simulations of this work, as well as, of the PEI’s, indicated that the southeast and southwest winds are determinant in the dispersion of the oil slick towards the mangroves of Sepetiba Bay. Simulations with winds in these directions were the only ones to reach the mangrove areas.